Changes in annual tuberculosis notification rates between 1978/79 and 1983 for the population of Indian subcontinent ethnic origin resident in England. Issue 4 (December 1986) - Nunn, A J; Darbyshire, J H; Fox, W; Johnson, D A; Springett, V H
Abstract : In two national surveys of tuberculosis notifications in England conducted in 1978/79 and 1983 the estimated annual notification rates for the Indian subcontinent (Indian, Pakistani, and Bangladeshi) ethnic groups were considerably higher than the rate for the white ethnic group. The mean annual decline in rates between the surveys appeared to be greater for the Indian and the Pakistani and Bangladeshi ethnic groups, 15% and 16% respectively, than for the white ethnic group (7%). Data from two small sample population surveys, the National Dwelling and Housing Survey in 1978 and the Labour Force Survey in 1983, were used to calculate the rates. However, comparison of the estimates for the population of Indian subcontinent ethnic origin in England from these surveys revealed discrepancies between them. Additional information from the Labour Force Survey on the year of first entry to the United Kingdom (UK) permitted the calculation of new estimates for the 1978 population, and based on these estimates the annual notification rates for 1978/79 were 287 per 100, 000 for the Indian and 286 per 100, 000 for the Pakistani and Bangladeshi ethnic groups. The rates for 1983 were 178 and 169 respectively, and the mean annual decline between the surveys was 11% for the Indian and 12% for the Pakistani and Bangladeshi ethnic groups. There were important changes in the characteristics of the population of Indian subcontinent ethnic origin in England between 1978 and 1983, and therefore the rates for both surveys have been standardised by the method of direct standardisation to a common reference population. Standardizing for year of entry to the UK, place of birth (UK or abroad), age, and sex reduced the mean annual decline in the notification rate to 4% for the Indian and 9% for the Pakistani and Bangladeshi ethnic groups. The much greater reduction in the rate of decline in the Indian ethnic group is due to the substantial decline between the surveys in the proportion of recent immigrants, the group with the highest annual notification rate, in that population. Future trends will continue to be influenced by immigration patterns, but it will also be important to monitor the rates among the increasing proportion of the population born in the UK or resident in England for more than five years.